Multigram Synthesis of Difluoromethylene Phosphonic and Phosphinic Amides and Phosphine Oxides via Formal [2,3]-Sigmatropic Allyl Phosphite–Allylphosphonate Rearrangement - Shevchuk, Michael; Röschenthaler, Gerd-Volker (Synthesis, 2021)
We describe a method for the preparation of CF2-P(V) building blocks and monomers for biological and materials chemistry applications in multigram quantities based on a formal [2,3]-sigmatropic phospha-Wittig rearrangement of readily available fluoroallyl bis(amido)phosphites, amido(aryl)phosphonites, and diarylphosphinites. The proposed intramolecular phosphorylation approach complements the currently prevailing phosphoryldifluoromethylation methods by providing a straightforward access to difluoromethylene phosphonate analogues bearing dialkylamino and/or aryl substituents at the phosphoryl group. An important advantage of the developed method is that it does not rely on ozone-depleting HCF2Cl and CF2Br2 necessary for the preparation of phosphoryldifluoromethylating reagents. 2,3,3-Trifluoroallyloxy P(III) derivatives substituted with two dialkylamino and/or aryl groups underwent a facile [2,3]-rearrangement to give difluoromethylene phosphonic and phosphinic amides and phosphine oxides on up to a 0.15 mol (30 g) scale. The reaction was extended to P(III) derivatives of 1-substituted 2,3,3-trifluoro- and 3,3-difluoroallylic alcohols readily available from carbonyl compounds and, respectively, 1,1,1,2-tetrafluoroethane and O-protected 2,2,2-trifluoroethanols. Products derived from O-(tetrahydropyran-2-yl)-2,2,2-trifluoroethanol were synthesized and deprotected in a one-pot multistep protocol to give phosphonic and phosphinic amide and phosphine oxide analogues of α,α-difluoro-β-ketophosphonates on a multigram scale.
Keywords: phosphonates; phosphinates; phosphine oxides; phosphonic amides; fluoroallyl; difluoromethylene; ketones; [2,3]-rearrangement